2015
DOI: 10.1186/s40246-015-0039-x
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale population structure of Malays in Peninsular Malaysia and Singapore and implications for association studies

Abstract: Fine scale population structure of Malays - the major population in Malaysia, has not been well studied. This may have important implications for both evolutionary and medical studies. Here, we investigated the population sub-structure of Malay involving 431 samples collected from all states from peninsular Malaysia and Singapore. We identified two major clusters of individuals corresponding to the north and south peninsular Malaysia. On an even finer scale, the genetic coordinates of the geographical Malay po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This finding aligns with a previous study that revealed a significant relationship between the severity of fatigue and ethnicity among breast cancer survivors [ 17 ]. Hoh et al [ 63 ] showed in their trial that the high association between the ethnicity of patients, particularly Malay patients, and fatigue severity might be due to the fact that Malays constitute the predominant racial group in Malaysia. The data also demonstrated a statistically significant ( p <0.005) association between fatigue severity and breast cancer stage.…”
Section: Discussionmentioning
confidence: 99%
“…This finding aligns with a previous study that revealed a significant relationship between the severity of fatigue and ethnicity among breast cancer survivors [ 17 ]. Hoh et al [ 63 ] showed in their trial that the high association between the ethnicity of patients, particularly Malay patients, and fatigue severity might be due to the fact that Malays constitute the predominant racial group in Malaysia. The data also demonstrated a statistically significant ( p <0.005) association between fatigue severity and breast cancer stage.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the clinical epidemiology and laboratory aspects of ITP can contribute to the diagnosis and optimization of patient care, besides providing direction for further studies on the pathophysiology and the development of a gold standard test. Given Malaysia's diverse population, which includes people of various ethnicities and genetic backgrounds [ 18 ], more research is needed to understand potential differences in the prevalence and clinical presentation of ITP among different demographic groups. Therefore, conducting a study in the northeastern Malaysian population can provide a more comprehensive picture of the variation of the clinical pathogenicity of ITP in Malaysia.…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirms that the prevalence of Malay ITP patients is the highest compared to other ethnic groups (Chinese and Indian), as reported by previous local studies in Perak and Selangor [ 9 , 14 ]. About 63% of the total population in Peninsular Malaysia is constituted by Malays [ 18 ], thus establishing their dominance in the research.…”
Section: Discussionmentioning
confidence: 99%
“…Several cohort studies have developed SULT1E1 association models, such as Predictors of Breast Cancer Recurrence (ProBeCaRE) [ 90 ] and U-statistics-based tests for identifying the pathway-based candidate genes of breast cancer and hormone metabolism pathways [ 91 ]. In addition, an intronic polymorphism (rs3775779) was discovered as a marker for analyzing the ethnic difference in the fine-scale population structure of Malays in Peninsular Malaysia and Singapore [ 92 ]. These studies suggest diverse scientific approaches to figure out the role of SULT1E1.…”
Section: Future Directions For Clinical Integrationsmentioning
confidence: 99%